Peran Kepala Kampung Dalam Pembangunan Kampung Ngenyan Asa di Kecamatan Barong Tongkok Kabupaten Kutai Barat - Agus Fransisko Doran (Universitas 17 Agustus 1945 Samarinda, 2020)
The purpose of this study was to determine the role of village head in running the village development and to identify factors inhibiting the village head in carrying out development in Kampung Ngenyan Asa Barong Tongkok District West Kutai. Type of research included qualitative descriptive. The focus of research defined the role of Head of Kampung indicators: governance, village development, develop the economic life of the community, village head inhibiting factor in implementing development in Kampung Ngenyan Asa districts Barong Tongkok West Kutai. While the source of the data taken from informed competent, among which: Kampung Secretary, Staff / Employee Ngenyan Asa Kampung Office whose duties related to the research problem under investigation and the public. While data collection techniques by observation, interviews, and documentation. Analysis of the data used is an interactive model developed. The results showed that the administration of the village and community development is done in the village hall. Realization of democracy in village administration official elements of village government. The village headman to supervise the implementation of the rules and regulations of the village chief. Government administration office is rarely open and difficult village chief in my hometown for meet if you want to take care of the home secretary of the village. Village Development is a deliberate change of the Head and the people in the village, in the form of facilities and infrastructure that can improve people's welfare as planned by the village head to the public. Economic life of the community in terms of economic and social order is good enough, either from outside or from within the village. Head of the village is a driving force of development in social and economic fields means the existence of village headman function mobilize the community in doing something actions or activities to co-develop the economic life of the people in development. Tujuan dari penelitian ini adalah untuk mengetahui peran kepala desa dalam menjalankan pembangunan desa dan untuk mengidentifikasi faktor-faktor yang menghambat kepala desa dalam melaksanakan pembangunan di Kampung Ngenyan Asa Barong Tongkok Kecamatan Kutai Barat. Jenis penelitian termasuk deskriptif kualitatif. Fokus utama penelitian mendefinisikan peran Kepala Indikator Kampung: tata kelola, pembangunan desa, pengembangan kehidupan ekonomi masyarakat, faktor penghambat kepala desa dalam melaksanakan pembangunan di Kampung Ngenyan Asa kecamatan Barong Tongkok Kutai Barat. Sedangkan sumber data yang diambil dari informed competent, di antaranya: Sekretaris Kampung, Staf/Karyawan Kantor Kampung Asa yang tugasnya terkait masalah penelitian yang sedang diselidiki dan masyarakat. Sedangkan teknik pengumpulan data dengan observasi, wawancara, dan dokumentasi. Analisis data yang digunakan adalah model interaktif yang dikembangkan. Hasil penelitian menunjukkan bahwa administrasi pembangunan desa dan masyarakat dilakukan di balai desa. Terwujudnya demokrasi dalam unsur pemerintahan desa pemerintah desa. Kepala desa untuk mengawasi pelaksanaan aturan dan peraturan kepala desa. Kantor administrasi pemerintahan jarang buka dan sulit kepala desa di kampung halaman saya untuk ke temui jika ingin mengurus rumah sekretaris desa. Pembangunan Desa merupakan perubahan yang disengaja dari Kepala desa dan masyarakat di desa, berupa sarana dan prasarana yang dapat meningkatkan kesejahteraan masyarakat sesuai rencana kepala desa kepada masyarakat. Kehidupan ekonomi masyarakat dari segi tatanan ekonomi dan sosial sudah cukup baik, baik dari luar maupun dari dalam desa. Kepala desa merupakan motor penggerak pembangunan di bidang sosial dan ekonomi berarti adanya fungsi kepala desa menggerakkan masyarakat dalam melakukan sesuatu tindakan atau kegiatan untuk bersama-sama mengembangkan kehidupan ekonomi masyarakat dalam pembangunan